Improving the Coordination of Humanitarian Relief Supply Chains: The 2010 Haiti Crisis Case Study - Lamlenn, Laura L (2010)
Abstract Purpose –The purpose of this research is to explore the difficulties faced in humanitarian supply chain coordination and come out with suggested initiatives which are deemed to improve coordination amid international and local relief agencies and NGO’s responding to a crisis situation Design/methodology/approach – The proposed improvement analysis will be based on the case study of the post-disaster response 2010 Haitian Earthquake. It contains a literature review of commercial and humanitarian supply chain literature as well as a review of Pettit and Beresford (2006) framework of supply chain Critical Success Factors, which was used as a framework of analysis in chapter 4. The methodology used were borrowed aspects(coding procedures and paradigm) of Strauss and Corbin’s (1990) grounded theory which was supported by data collected from primary sources (survey and interviews) and secondary sources. The results are presented after each analysis chapter. Findings – Attention was drawn to 3 main causes of the coordination problems experienced: poor preparedness and strategic planning on the part of Haitian government and UN agencies , unclear accountability lines and lack of experienced personnel. This where the main points around which the lessons to be learned were drawn: Improving national preparedness, improving strategic planning, the need for more experienced personnel Improving overall humanitarian coordination and the missed opportunities: exploiting relationships with the private sector Originality/value –The situation in Haiti was different from other large scale crisis, thus the examination of problems experienced in this unique situation should reveal new lessons to be learned for better coordination in the future. As such, this study provided a comprehensive analysis of this problems in the light of very critical success factors within a relief chain and recommends some improvement initiatives and missed opportunities which can be considered for future adoption and where necessary future investigation. Keywords—Coordination, Relief chain, Humanitarian, Supply chain management, disaster/crisis